Recanalization using direct stenting before bowel resection for acute-on-chronic superior mesenteric artery occlusion: A case report. (2020) - Suzuki, Toshinao; Murata, Satoru; Tsunoyama, Taichiro; Kitamura, Maki
Highlights: Early notice of acute-on-chronic mesenteric ischemia leads to improved survival. Endovascular recanalization and surgery may be effective for this type of ischemia. Direct stenting could save time of recanalization. As recanalization time is saved, it leads to less distal embolization risk. Abstract: Introduction: Acute-on-chronic mesenteric ischemia (ACMI) refers to acute mesenteric ischemia (AMI) developing in a patient displaying typical symptoms of chronic mesenteric ischemia (CMI). Delayed treatment can cause short bowel syndrome and increased mortality. Intervention involves intestinal revascularization and resection of the necrotic intestine. However, the revascularization procedure must consider the chronic nature of the occlusion. Presentation of case: A 79-year-old man presented with periumbilical pain for 6 h. AMI was diagnosed, together with chronic superior mesenteric artery occlusion and suspected intestinal necrosis. The symptomatic CMI might have insufficient blood flow to intestines. Endovascular recanalization of the superior mesenteric artery using direct stenting was performed before laparotomy to improve blood flow to the intestines. Subsequent laparotomy revealed approximately 60 cm of ischemic small bowel extending from the jejunum (300 cm anal to the ligament of Treitz) to the ileum (30 cm oral to the terminal ileum). The necrotic bowel was resected without anastomosis. At the second-look operation, further resection was not required. Discussion: Making a differential diagnosis between acute and acute-on-chronic occlusions is essential for determining the necessity of recanalization and the method of restoring the intestinal blood flow. Here, the patient with symptomatic CMI might have had insufficient blood flow to the intestines despite establishing collateral supply. We determined that recanalization was needed. Direct stenting without predilation could save time to recanalization and result in less risk of distal embolization. Conclusion: This case suggests prompt recanalization using direct stenting can minimize subsequent bowel resection in patients with ACMI.